The Effect of Debt Policy, Profitability, and Tax Avoidance on Firm Value with Dividend Policy as a Moderating Variable in Energy Sector Companies Listed on the Indonesia Stock Exchange During the 2018–2022 Period - Windy Dwi Oktavia (International Journal of Social, Economic, and Business, 2025)
This study aims to determine the effect of debt policy, profitability, and tax avoidance on firm value, with dividend policy as a moderating variable, in energy sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2018-2022. The data used is quantitative, sourced from secondary data. The population consists of 59 energy sector companies listed on the IDX from 2018 to 2022. The sampling technique used is purposive sampling, resulting in a sample of 21 companies. Data analysis was performed using path analysis with the assistance of AMOS 24 software. The results indicate that debt policy does not have a significant impact on firm value. Profitability has a significant positive effect on firm value. Tax avoidance has a significant negative impact on firm value. Dividend policy does not significantly moderate the effects of debt policy, profitability, and tax avoidance on firm value. Therefore, companies in the energy sector should focus on their profitability levels, as it positively influences firm value. Additionally, energy sector companies should avoid tax avoidance practices, as they negatively impact firm value.